2003
DOI: 10.2337/diabetes.52.5.1300
|View full text |Cite
|
Sign up to set email alerts
|

Association and Haplotype Analysis of the Insulin-Degrading Enzyme (IDE) Gene, a Strong Positional and Biological Candidate for Type 2 Diabetes Susceptibility

Abstract: The gene for insulin-degrading enzyme (IDE) represents a strong positional and biological candidate for type 2 diabetes susceptibility. IDE maps to chromosome 10q23.3, a region linked to diabetes in several populations; the rat homolog has been directly implicated in diabetes susceptibility; and known functions of IDE support an important role in glucose homeostasis. We sought evidence for association between IDE variation and diabetes by mutation screening, defining local haplotype structure, and genotyping v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 26 publications
2
27
3
Order By: Relevance
“…30 Here, we found a novel association of rs11187007 with type 2 diabetes and triglycerides, in line with the findings that variants and haplotypes in IDE were associated with FPG, HbA1c and type 2 diabetes. 22,23,30,31 On the other hand, the association study and meta-analysis further confirmed the effect of HHEX rs1111875 on type 2 diabetes in Chinese population, consistent with previous genome-wide association studies and replication studies in other ethnic populations. [15][16][17][18][19]25,26,[32][33][34] The HHEX gene encodes a transcription factor that is also involved in the Wnt signaling pathway and that has been shown to be essential for pancreas development.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…30 Here, we found a novel association of rs11187007 with type 2 diabetes and triglycerides, in line with the findings that variants and haplotypes in IDE were associated with FPG, HbA1c and type 2 diabetes. 22,23,30,31 On the other hand, the association study and meta-analysis further confirmed the effect of HHEX rs1111875 on type 2 diabetes in Chinese population, consistent with previous genome-wide association studies and replication studies in other ethnic populations. [15][16][17][18][19]25,26,[32][33][34] The HHEX gene encodes a transcription factor that is also involved in the Wnt signaling pathway and that has been shown to be essential for pancreas development.…”
Section: Discussionsupporting
confidence: 74%
“…For the HHEX-IDE locus, only representative SNPs with r 2 o0.80 based on HapMap Han Chinese were selected for genotyping, and eight variants (rs1111875, rs2275729, rs5015480, rs7923837, rs1887922, rs2209772, rs1999763 and rs11187007) which had positive association with type 2 diabetes or diabetes-related traits in previous studies were selected. [15][16][17][18][22][23][24][25][26] Genotyping All 13 variants were genotyped using TaqMan genotyping assay on an ABI7900 system (Applied Biosystems, Foster City, CA, USA). Genotyping success rates were above 95% except rs12779790 and all mismatch rates were below 1% in duplicate samples.…”
Section: Snps Selectionmentioning
confidence: 99%
“…Association study. To estimate the sample size required to replicate the main single-SNP association with type 2 diabetes of Groves et al (8) (SNP rs4646953), we assumed a minor allele frequency of 23%, a type 2 diabetes disease prevalence of 8%, and a genotypic relative risk of 1.2 in a multiplicative model. Under these parameters, we estimated that our combined sample of 1,112 case-control pairs would provide Ͼ80% power to reject the null hypothesis of no association at P Ͻ 0.05; this power is further raised by the inclusion of the family-based samples.…”
Section: Resultsmentioning
confidence: 99%
“…Written informed consent was obtained from each patient, and DNA extraction was performed using a standard phenol-chloroform procedure. The UK samples comprised 590 cases with type 2 diabetes enriched for positive family history (probands from the Diabetes UK Warren 2 repository) (Wiltshire et al 2001) and 549 UK population controls (the ECACC-HRC collection) (Groves et al 2003).…”
Section: Methodsmentioning
confidence: 99%